Ultrasound-assisted enzymatic indirect determination of total 3-monochloropropane-1, 2-diol esters in canned fish oil fraction. (1st March 2023) - Custodio-Mendoza, Jorge Antonio; Ramos, Andrea; Lorenzo, Rosa Antonia; Carro, Antonia M.
Highlights: Indirect determination of total 3-monochloropropane-1, 2-diol esters in canned fish. Enzymatic lipolysis by aims of Burkholderia cepacia lipase enhanced by ultrasound. First occurrence study of chloropropanol esters in the oil fraction of canned fish. 41 analyzed samples including Albacore, Atlantic saury, Mackerel, Melva, Sardine, and Tuna. The presence of 3-MCPDE was confirmed in all the analyzed samples. Abstract: A novel, fast, and cost-effective indirect enzymatic method was successfully developed to assess the total 3-monochloropropane-1, 2-diol (3-MCPD) in canned food's oil fraction by the action of Burkholderia cepacia lipase. The total 3-MCPD were derivatized with n -Heptafluorobutyrylimidazole (HFBI) for GC–MS analysis during dispersive liquid–liquid microextraction (DLLME). An asymmetrical 2 2 1 3 //8 screening design was used to study the influence of critical factors on the method's effectiveness. The analytical features of the proposed method were assessed following Food and Drug Administration (FDA) guidelines using extra virgin olive oil (EVOO) as a blank sample. Outstanding results were achieved in terms of linearity (r 2 = 0.9995), sensitivity, precision (2.1 % to 10.4 % RSD), and accuracy (98.7 % ≤ recovery ≤ 101.9 %). Method efficacy was tested by comparing the results of 10 edible oils for total 3-MCPD with those reported in previous works. A total of 41 samples were analyzed. The lowest 3-MCPD content was found in samples of albacore canned in EVOO oil, while the highest amounts were found in albacore, mackerel, and Atlantic saury samples, all preserved in refined sunflower oil.